2021
DOI: 10.1507/endocrj.ej20-0630
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective exploratory analyses on gender differences in determinants for incidence and progression of diabetic retinopathy in Japanese patients with type 2 diabetes mellitus

Abstract: Gender differences in risks for macrovascular complications in type 2 diabetes mellitus (T2DM) have been well established. However, the impact of gender differences on diabetic retinopathy (DR) has not been fully elucidated. We therefore retrospectively explored gender-specific determinants for DR in patients with T2DM in a small sized Japanese cohort in Okinawa. There were 214 patients who were diagnosed as no DR (n = 142) and non-proliferative DR (n = 72) in 2009. During the follow-up of median 7 years, 41/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
(37 reference statements)
2
9
0
Order By: Relevance
“…This result was consistent with majority studies [9,11,28]. However, several articles showed opposite result that NPDR group had lower UA level in plasma compared with NDR group [13,37]. One reason may be the coverage error caused by the NPDR patients who lost follow-up due to slow DR progression and normal vision [13].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This result was consistent with majority studies [9,11,28]. However, several articles showed opposite result that NPDR group had lower UA level in plasma compared with NDR group [13,37]. One reason may be the coverage error caused by the NPDR patients who lost follow-up due to slow DR progression and normal vision [13].…”
Section: Discussionsupporting
confidence: 88%
“…However, several articles showed opposite result that NPDR group had lower UA level in plasma compared with NDR group [13,37]. One reason may be the coverage error caused by the NPDR patients who lost follow-up due to slow DR progression and normal vision [13]. Another reason is the exclusion of NPDR patients with moderate or severe DME [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for three studies ( 28 , 34 , 39 ) that measured UA concentrations using plasma, serum was utilized for the measurement of UA concentrations in other studies. Eleven studies ( 20 , 22 , 29 , 34 , 35 , 37 40 , 43 , 44 ) that scored 7 or higher were considered high quality, and others ( 23 , 28 , 30 – 33 , 36 , 41 , 42 , 45 ) scored from 4 to 6, indicating that the overall quality of the studies was acceptable. The participants' characteristics, including age, sex, and BMI, are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Prior research on sex-dependent associations of SUA with diabetes mellitus and its complications has been documented. 22 , 33 , 34 Although hyperuricemia poses an increased risk of developing diabetes mellitus in both sexes, females with hyperuricemia are more likely to develop diabetes than males with hyperuricemia. 35 A Japanese study showed that higher SUA levels are associated with an increased risk of new-onset diabetic retinopathy in male patients but not in female patients.…”
Section: Discussionmentioning
confidence: 99%